PENGARUH RESIKO AUDIT, INDEPEDENSI, KOMPETENSI, MOTIVASI, DAN BATASAN WAKTU TERHADAP KUALITAS HASIL AUDIT (STUDI EMPIRIS PADA KAP WILAYAH JAMBI, PEKANBARU DAN BATAM) - . Badewin; Afrizal; Susfayetti (Jurnal Akuntansi & Keuangan Unja, 2016)
The aim of this research is (1) To get emirically proof the influence of audit risk, independence, competence, motivation and range of time partially to wards the improvement of audit guality, (2) To get the empirical proof whether audit risk, independence, competence, motivation and range of time simultaneously towards the improvement of audit quality. This research is a survey research with giving guestioaires directly to sampel. The population in this research is all auditors who work on public accoutant office in Jambi, Pekanbaru and Batam district. The sampel technique which is used in this research is saturated samples, it is a technique of taking sampel if all population to be the sample.The amount of sampel are 95 auditors, based on the total of population. There are 95 questionaires are given to each leader of KAP but only 72 questionaires are returned. The data analisis technigue used multiple linear regretion analysis tecnigue used multiple linear regretion analysis by using SPSS 19.00 for Windows the result of this research showed that (1) Audit risk, independence, competence, motivation and range of time partially give influence towards audit quality. (2) audit risk, independence, compentence, motivation and range of time simultanneously also influence audit of quality.